Authentic and Hubristic Pride as Assessed by Self, Friends, and Strangers. (September 2016) - Liu, Conghui; Yuan, Li; Chen, Chuansheng; Yu, Guoliang
Previous research has distinguished authentic and hubristic facets of pride, which can be assessed by the Authentic and Hubristic Pride Scales (AHPS). To examine the relations between self-ratings and others' ratings of pride, this study recruited 110 participants and obtained their self-ratings on the AHPS and ratings by two friends and three strangers in a round-robin design. In addition, participants' social status was self-reported and their leadership style (dominance vs. prestige) was evaluated by friends and strangers. Results revealed higher self-friend agreement than self-stranger agreement on authentic pride and higher friend–stranger agreement than self-other (friend and stranger) agreement on hubristic pride, suggesting that authentic pride is noticed by close friends as well as oneself, but hubristic pride is obvious only to others. Consistent with this, there was also some evidence that other-rated hubristic pride was significantly associated with social status and dominant leadership style.